ANALISIS PENERAPAN PENDIDIKAN MULTIKULTIURAL TERHADAPA PERILAKU SOSIAL SISWA SEKOLAH DASAR - 'Azizah, Wida Nurul (Journal of Professional Elementary Education, 2024)
Multicultural education is very important for elementary school students because it opens the door to shaping their social behavior. The purpose of this article is to determine the application of multicultural education to the social behavior of elementary school students. The type of research used is qualitative research with the research approach used, namely library research. The results of the article on the application of multicultural education to the social behavior of elementary school students, namely: the values ​​of tolerance, equality, democracy and justice which are in accordance with the development of culture and diversity which form intelligent, skilled and characterful behavior that can be realized in everyday life elementary school students.